Rock sparrow song reflects male age and reproductive success. - Erwin Nemeth (Public Library of Science (PLoS), 2012)
The evolution of mating signals is closely linked to sexual selection. Acoustic ornaments are often used as secondary sexual traits that signal the quality of the signaller. Here we show that song performance reflects age and reproductive success in the rock sparrow (Petronia petronia). In an Alpine population in south-east France, we recorded the songs of males and assessed their genetic breeding success by microsatellite analysis. In addition to temporal and spectral song features, we also analysed for the first time whether the sound pressure level of bird song reflects reproductive success. Males with higher breeding success sang at a lower rate and with a higher maximum frequency. We found also that older males gained more extra-pair young and had a higher overall breeding success, although they also differed almost significantly by having a higher loss of paternity in their own nests. Older males could be distinguished from yearlings by singing at lower rate and higher amplitudes. Our findings suggest that song rate may be used as a signal of age and together with song pitch as a signal of reproductive success in this species. Alternatively, younger and less successful males might try to compensate their inferior status by increased song rates and lower pitch. Independent of age and quality, high-amplitude songs correlated with paternity loss in the own nest, suggesting that in this species song amplitude is not an indicator of male quality but high-intensity songs may be rather a response to unfaithful social mates.